2008
DOI: 10.1136/bjo.2008.138123
|View full text |Cite
|
Sign up to set email alerts
|

Plusoptix Vision Screener: the accuracy and repeatability of refractive measurements using a new autorefractor

Abstract: The PVS may underestimate children's refractive error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 16 publications
2
38
2
2
Order By: Relevance
“…In the study of Dahlmann-Noor et al , the repeatability coefficient was about 0.6 D, although only 35% of retinoscopy and Plusoptix results were within ±1.0 D of each other (74% in our study) 5. This shows the good repeatability of the instrument.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In the study of Dahlmann-Noor et al , the repeatability coefficient was about 0.6 D, although only 35% of retinoscopy and Plusoptix results were within ±1.0 D of each other (74% in our study) 5. This shows the good repeatability of the instrument.…”
Section: Discussionsupporting
confidence: 48%
“…Schimitzek and Lagrèze noted a 0.73 D shift to myopia due to uncontrolled accommodation 9. Dahlmann-Noor et al reported a myopic shift of 1.9 D 5. These findings show the possibility of uncontrolled accommodation in patients who were examined by the Plusoptix, which according to the findings of Schimitzek and Haase and of Schaeffel et al cannot be relieved by using cycloplegic drops or 3 D glasses 10 11.…”
Section: Discussionmentioning
confidence: 77%
“…15,16,28,29 Several studies have compared agreement between the plusoptix and CR performed by an orthoptist or an ophthalmologist. 17,20,30 For reasons of cost-effectiveness, it would be preferable to screen large populations with lay screeners. In the present study, all measurements were made by 1 lay screener, but this was not possible for CR due to the complexity of the test.…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to reduce interobserver variability for the gold standard by performing the same battery of tests on all subjects and by following referral criteria laid down at the beginning of the study. As for the PVS, we determined intra- and interobserver variability of measurements as part of a separate study into device reliability and accuracy18 and can exclude any significant influence. Lastly, with view to the comparison of refractive data, our results are similar to those reported by other studies 19 – 21…”
Section: Discussionmentioning
confidence: 99%